2015
DOI: 10.3171/2014.9.peds14213
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumors of the brainstem in children treated according to the HIT trials: clinical findings of a rare disease

Abstract: OBJECT Primitive neuroectodermal tumors of the central nervous system (CNS-PNET) arising in the brainstem are extremely rare, and knowledge about them is limited. The few existing case series report fatal outcomes. The purpose of this study was to analyze clinical characteristics of and outcome for brainstem CNS-PNET patients treated according to the consecutive, population-based HIT studies covering a 19-year time period. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Seventeen patients were included in this series: 11 male and 6 female, with a median age at the time of the reirradiation of 14.0-years CI 95%. [12][13][14][15][16][17] Among those reirradiated the median of time of disease relapse was 8 to 9-years from the first to the second irradiation. Four patients received CS plus tumor volume reirradiation, while the rest only to the primary site of recurrence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen patients were included in this series: 11 male and 6 female, with a median age at the time of the reirradiation of 14.0-years CI 95%. [12][13][14][15][16][17] Among those reirradiated the median of time of disease relapse was 8 to 9-years from the first to the second irradiation. Four patients received CS plus tumor volume reirradiation, while the rest only to the primary site of recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…11,17,19 During their evolution, there are relapses, that could occur a few months to years after the first irradiation. 9,[13][14][15] Rao et al 8 reported reirradiation in 67 children with recurrent CNS malignancies and found that the median overall survival after the completion of repeated radiation therapy (RT) was 12.8-months for the entire cohort and concluded that CNS reirradiation could be a reasonable treatment option. In our study, a similar range of median overall survival was obtained (12.2-months).…”
Section: Discussionmentioning
confidence: 99%
“…There are but a few case reports or small case series in the literature of embryonal tumors, with the most commonly described example of this group being a primitive neuroectodermal tumor (PNET). 1,4,[12][13][14]38,40,44 We present our experience with these unusual and challenging neoplasms.…”
mentioning
confidence: 97%
“… 2 To date, few effective approaches are available to improve the prognosis of patients. 3 Therefore, a comprehensive analysis is needed to discover biomarkers of the disease and small molecule drugs that can improve the patients’ treatment strategy.…”
mentioning
confidence: 99%
“…Accompanied by the low incidence rate, it features high-lever of malignancy, rapid progress, high recurrence and metastasis rate, and poor prognosis 2. To date, few effective approaches are available to improve the prognosis of patients 3. Therefore, a comprehensive analysis is needed to discover biomarkers of the disease and small molecule drugs that can improve the patients’ treatment strategy.…”
mentioning
confidence: 99%